2022
DOI: 10.1021/acsomega.2c06437
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Study of Imidazole-Type Deep Eutectic Solvents for Efficient Absorption of CO2

Abstract: Deep eutectic solvents (DESs) are a new class of green solvents that exhibit unique properties in various process applications. In this regard, this study evaluated imidazole-type DESs as solvents for carbon dioxide (CO2) capture. A series of imidazole-type DESs with different ratios was prepared through one-step synthesis. The absorption capacity of CO2 in imidazole-type DESs was measured through weighing, and the effects of temperature, hydrogen bond acceptors, hydrogen bond donors, and water content were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The H-bonding network influences the viscosity of the DES, which is an essential factor in deciding how easily CO 2 can diffuse through the solution before reacting. 21,65 Experimental techniques, such as infrared spectroscopy (FT-IR), provide valuable insights into H-bonding.…”
Section: Inferences Of Experimental Datamentioning
confidence: 99%
“…The H-bonding network influences the viscosity of the DES, which is an essential factor in deciding how easily CO 2 can diffuse through the solution before reacting. 21,65 Experimental techniques, such as infrared spectroscopy (FT-IR), provide valuable insights into H-bonding.…”
Section: Inferences Of Experimental Datamentioning
confidence: 99%
“…During the last decades, 30-50 wt % monoethanolamine (MEA) aqueous solutions have been industrially used for the CO 2 capture, mainly thanks to the reversible chemical formation of carbamates. [34,39] Recently, amine-based DES containing in their composition different di-and monoethanolamines, [41,42] functionalized-DES possessing CO 2 affinity groups, [43] as well as imidazole-based DES, [44] have been developed for enhancing the CO 2 capture capacity with respect to traditional MEA solutions. [20,45] This is because these novel DES are able to display both a chemical reaction and additional Van der Waals interactions with CO 2 , which notably enlarge the amount and efficiency of the mechanisms for the CO 2 capture, with respect to the use of molecular solvents or imidazolium-based ILs.…”
Section: Ionic Solvents: Types and Featuresmentioning
confidence: 99%
“…CO 2 Absorption by DESs of Imidazole as HBA and Amines as HBD. Shi et al 65 synthesized DESs using Im and 67 synthesized DESs for CO 2 absorption using 1H-1,2,4-triazole (Tz) as HBA and 1,5diazabicyclo[4.3.0]non-5-ene (DBN) as HBD in different ratios. The results indicate that Tz-DBN (1:3) has the highest absorption capacity, 1.90 mol of CO 2 /mol of DES.…”
Section: Co 2 Absorption By Choline-based Dess Synthesizedmentioning
confidence: 99%
“…Shi et al synthesized DESs using Im and 4CH 3 -Im as HBAs and DEA and MEA as HBDs in different ratios and determined their CO 2 absorption capacity. The results showed that Im-MEA (1:4) had the best absorption capacity (see Table for detailed data).…”
Section: Dess Directly As Absorbents For Co2 Absorptionmentioning
confidence: 99%